Challenges in policy reforms for non-communicable diseases: the case of diabetes in Kenya - Veronica Shiroya; Florian Neuhann; Olaf Müller; Andreas Deckert (Taylor & Francis Group, 2019)
Background: The 2011 UN declaration on non-communicable diseases (NCDs) recognized their importance as a global health issue, particularly for low- and middle-income countries. The extent to which these countries address policy implementation gaps in the face of resource limitations and competing priorities remains largely unexplored. Objective: This qualitative study presents Kenya's experience of translating the UN declaration to national policies for diabetes prevention and control. Methods: Policy documents published between 2006 and 2016 were analyzed. Thirty-two documents were included in the analysis. Interviews with six purposively selected policy stakeholders at multiple levels of decision-making were conducted. Emerging themes were deconstructed into a policy analysis triangle. Results: Diabetes-specific policies already existed in Kenya before 2011, suggesting successful advocacy work by diabetes interest groups. The 2011 UN declaration subsequently coincided with a period of political transition in Kenya, opening policy windows that the diabetes community leveraged to trigger political drive against prevailing challenges. The post-declaration period reflected a transition from diabetes-specific policies to a wider NCD agenda. Most of the documents and national strategies aligned strongly with international documents, however, were based on scant local evidence. The implementation process was largely health-sector driven. The non-health sector remained largely uninvolved, contrary to global recommendations. This, in addition to fragmented health governance and weak monitoring systems, continues to undermine existing gains and efforts to fight diabetes and NCDs on a wider scale. Conclusions: In Kenya, a major gap remains between how diabetes is addressed within the NCD policy agenda and tackling diabetes in reality, with respect to local implementation processes. More emphasis on population-wide prevention and inclusion of the non-health sector could help to cascade national efforts to the grassroots level. A concerted effort from the highest political level is needed to address overarching NCD drivers while maintaining health system improvement strategies.